Detection of Diplodia sapinea in Corsican pine seeds. (22nd July 2014) - Decourcelle, T.; Piou, D.; Desprez‐Loustau, M.‐L.
<x xml:space="preserve">Abstract</x> Diplodia sapinea is one of the major pathogens of pines worldwide. Despite the putative critical importance of seed infection in the epidemiology of the disease, this aspect of the biology of the fungus is poorly known. Here, biological and molecular methods were developed for the detection of the fungus and applied to assess D. sapinea infection in Corsican pine seeds. A buffered medium containing tannic acid and malt extract as a nutrient base was the most efficient and selective for D. sapinea recovery. A molecular method based on DNA extraction with a commercial kit and specific amplification, including an internal amplification control, was developed. A high percentage of infection (57% positive isolations) was observed in seeds obtained from fallen cones in a Corsican pine stand with no apparent symptoms of D. sapinea. Seeds collected from trees in a seed orchard showing severe symptoms of dieback caused by D. sapinea had comparatively lower infection (38%). Moreover, very low infection levels (1–5%) were observed after the standard treatment used for seed extraction, which included heating at 40°C. Diplodia sapinea was not recovered from seedlings grown from infected seed lots submitted to water stress. Overall, results suggest that the risk of disease transmission by commercial seeds is probably low, but could be further reduced by thermotherapy.